Treatment of Emesis Gravidarum in Pregnant Women with Lemon Aromatherapy (Citrus) - Yuliana, Ana; Ifalahma, Darah; Listyani, Tiara Ajeng; Rahmasari, Ikrima; Puspitasari, Rara Ayu; Wargani, Rizki Nugraha (Global Health Science Group, 2024)
Emesis gravidarum is a symptom of nausea and vomiting that occurs during pregnancy, usually in the first trimester. This symptom is common in 50-80% of pregnant women and begins around the 6th week of pregnancy. If emesis gravidarum is not treated immediately, it will progress to hyperemesis and can result in impaired fetal growth, the fetus dies in the womb and the fetus can experience congenital abnormalities. Non-pharmacological treatment of emesis gravidarum or complementary therapy has the advantage of being cheaper and having no pharmacological effects. One safe therapy is by giving lemon (citrus) aromatherapy. Objective: This study aims to determine the effectiveness of lemon (citrus) aromatherapy in reducing emesis gravidarum in pregnant women. Method: The research design uses an experimental method with a one group pretest-posttest design. The independent variable is lemon aromatherapy, the dependent variable is emesis gravidarum. The sampling technique used purposive sampling technique, a sample of 10 pregnant women in the 1st trimester. The research instrument used lemon aromatherapy media and Pregnancy Unique Quantification of Emesis (PUQE-24). The data analysis used was the t-test. Results: The research results showed that the average incidence of emesis gravidarum before therapy was given was 9.3 (moderate degree category), the average incidence of emesis gravidarum after therapy was given was 5.5 (mild degree category). The results of the analysis using the t-test were p-value < α, namely 0.000 < 0.05, which means that there was an effect of giving lemon (citrus) aromatherapy therapy on reducing emesis gravidarum. Conclusion: Giving lemon (citrus) aromatherapy therapy is effective in reducing emesis gravidarum in pregnant women in the first trimester.